2014
DOI: 10.1016/j.appdev.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Paternal autonomy restriction, neighborhood safety, and child anxiety trajectory in community youth

Abstract: Intrusive parenting, primarily examined among middle to upper-middle class mothers, has been positively associated with the presence and severity of anxiety in children. This study employed cross-sectional linear regression and longitudinal latent growth curve analyses to evaluate the main and interactive effects of early childhood paternal autonomy restriction (AR) and neighborhood safety (NS) on the trajectory of child anxiety in a sample of 596 community children and fathers from the NICHD SECYD. Longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 75 publications
4
9
0
Order By: Relevance
“…Consistent with our first hypothesis, youth anxiety symptoms decreased across the five waves of this study, which is in line with findings from the literature (Cooper-Vince et al, 2014; Gullone et al, 2001; Hale et al, 2008). In order to determine when it might be most beneficial to intervene with anxious youth who do have persistent anxiety, it is relevant to examine when CEA and DT exert their greatest influence on symptomatology.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our first hypothesis, youth anxiety symptoms decreased across the five waves of this study, which is in line with findings from the literature (Cooper-Vince et al, 2014; Gullone et al, 2001; Hale et al, 2008). In order to determine when it might be most beneficial to intervene with anxious youth who do have persistent anxiety, it is relevant to examine when CEA and DT exert their greatest influence on symptomatology.…”
Section: Discussionsupporting
confidence: 93%
“…Broadly, we hypothesized that: (1) anxiety symptoms would decrease over time, in line with previous research (e.g., Cooper-Vince et al, 2014; Gullone et al, 2001; Hale et al, 2008); (2) youth with higher levels of self-reported CEA, or lower levels of DT, would have higher anxiety symptoms than their peers across the five assessments; and (3) given that we expected low DT youth to be most reactive to CEA, we expected that DT would moderate the relations between CEA and anxiety, such that youth with lower DT scores and higher CEA scores would have the highest anxiety symptoms.…”
Section: Current Studysupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, the generalizability of findings to all parents is limited, as the present analyses included only mothers. Consistent with theoretical work positing fathers play a unique role in the etiology of child anxiety (Bögels & Phares, 2008), a separate analysis of fathers’ autonomy restricting parenting behavior in the NICHD SECCYD sample evidenced a divergent pattern with respect child anxiety (Cooper-Vince, Chan, Pincus, & Comer, 2013). Further work is needed to expand on these parenting differences and better understand specifically how different parenting roles (i.e., single parents, parents in same-sex relationships) may impact the relationship between parenting behavior and child anxiety.…”
Section: Discussionmentioning
confidence: 64%
“…Anxiety symptoms in healthy school-age children and adolescents typically decline across development (Cooper-Vince, Chan, Pincus, & Comer, 2014; Feng, Shaw, & Silk, 2008; Hale, Raaijmakers, Muris, van Hoof, & Meeus, 2008b; Keenan et al, 2009; Van Oort, Greaves-Lord, Verhulst, Ormel, & Huizink, 2009). For example, latent growth curve analyses in a community sample have suggested that anxiety decreases from 6–15 years of age, with a more rapid decline prior to age 9 (Cooper-Vince et al, 2014).…”
mentioning
confidence: 99%